Nilai Ekonomi Agrowisata Bumi Perkemahan Ranca Cangkuang - Ernah, Ernah; usuf, Ghina Amelia; Bagaskara, Fadil (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The tourism sector has become a new source of economic growth in various regions of Indonesia, including Bandung Regency, which has the second-highest number of tourist attractions in West Java. One developing tourism potential is nature-based agrotourism, such as the Ranca Cangkuang Camping Ground. This site offers various environmental service benefits expected to attract tourists. Since this natural-resource-based tourist attraction does not yet have a clear market value, this study aims to estimate its economic value using the Individual Travel Cost Method (ITCM). The study results show a consumer surplus value of IDR 72,000 per individual per visit and an economic value of the Ranca Cangkuang Camping Ground amounting to IDR 1,416,240,000 for the period from March 2024 to February 2025.